Tailoring Cu immobilized MCM-41-based mesostructured catalysts for selective hydrogenolysis of biomass-derived furfural - Leela Prasad, Yandrati (2024)
The CuO-supported MCM-41 catalysts were prepared using a simple incipient wet impregnation method. The catalysts were investigated for hydrogenation of furfural to furfuryl alcohol synthesis. Among all the catalysts, the 2.5% CuO/MCM-41 catalyst shows the best catalytic performance with 92.5% conversion and 89% selectivity of furfuryl alcohol at 210 °C. The catalyst also demonstrated a high turnover frequency (TOF) of 154.4 h−1. The 2.5% CuO/MCM-41 catalyst remained stable for up to 20 h during the time on stream.